مؤشرات الإنذار المبكر للأزمات المصرفية تطبيق على القطاع المصرفي السوري الخاص - المشعل ياسر; كوكش ربا فهمي (Latakia University Journal - Economic and Legal Sciences Series, 2013)
يشهد القطاع المصرفي على الصعيد الدولي تطورات مهمة في السنوات الراهنة في ظل تداعيات الأزمة المالية التي حصلت عام 2007، ولما كان القطاع المصرفي السوري جزءاً من الكيان المالي الدولي، سعت الباحثة إلى وضع تصور مبدئي للمؤشرات التي يمكن أن يتضمنها نظام الإنذار المبكر لهذا القطاع وذلك انطلاقاً من أهمية الرشد الاقتصادي الذي يستلزم الحيطة والحذر في مواجهة الأزمات المصرفية وضرورة وضع آلية ملائمة للإنذار. وقد تمثلت مقومات وضع هذا التصور في الآتي: 1) تحديد العوامل الحاكمة للأزمات المصرفية والتي تمثلت بكل من المؤشرات الاقتصادية ومؤشرات الأداء المالي، وقد تبين من خلال الدراسة أن مؤشر الأزمة المصرفية يرتبط بعلاقة طردية مع نسبة عجز الموازنة العامة إلى إجمالي الناتج المحلي، وبعلاقة عكسية مع كل من درجة السيولة ومعدل العائد على الموجودات وكفاية رأس المال بالإضافة إلى تقلبات سعر الصرف. 2) تحليل أداء القطاع المصرفي السوري حيث تبين أنه يتمتع بكفاءة جيدة نسبياً خلال فترة الدراسة. The banking sector, at the international level, is witnessing important developments in recent years under the fallout of the financial crisis which happened in 2007, and what was for the Syrian banking sector as part of the international financial entity, the researcher strived to set a preliminary visualization of the indicators that can be Contained in an early warning system for this sector and based on the importance of economic wisdom which requires caution and carefulness when facing banking crises and the need to develop national mechanism suitable for warning. And the Constitutes in setting this visualization was represented in the following: 1- Identifying the factors governing crises banking, which were represented in all of the economic Indicators and financial performance Indicators, and in this study, it was found that Indicator of banking crisis is positively related with the public DTG get deficit to GDP, and an inverse relationship with the liquidity, return on the assets, financial solvency, additional to exchange rate risks. 2- Analysis of the performance of the Syrian banking sector showed that the sector has “relatively” good efficiency during the study period